2015
DOI: 10.1039/c4dt03319a
|View full text |Cite
|
Sign up to set email alerts
|

Assembling anionic Sb(v)/(iii) containing polyoxostibonates stabilized by triphenyltellurium cations

Abstract: Reactions of diphenyltellurium oxide with organostibonic acid and polymeric triphenylantimony oxide have been investigated independently. Single crystal X-ray diffraction studies have revealed the formation of novel and rare mixed valent Sb(v)/(iii) containing polyoxostibonates {(C6H5)3Te}2{Na2(H2O)2(p-Br-C6H4Sb(V))10(Sb(III))4[(C6H5)2Te]4(O)30(OH)4} and {(C6H5)3Te}4{[(C6H5)2Sb(V)]4(Sb(III))4(O)12(OH)4} . Solution (125)Te NMR supports the solid state structures presented. Interestingly, during the assembly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The idea was to synthesize the molecular complexes in unusual architectures using these ligand systems. We have previously reported a series of Organoantimony­(V) complexes based on less bulky phosphinate, phosphonate and selenate ligand systems . Herein, the synthesis of two organobismuth phosphinate complexes using different organobismuth precursors are reported.…”
Section: Introductionmentioning
confidence: 78%
“…The idea was to synthesize the molecular complexes in unusual architectures using these ligand systems. We have previously reported a series of Organoantimony­(V) complexes based on less bulky phosphinate, phosphonate and selenate ligand systems . Herein, the synthesis of two organobismuth phosphinate complexes using different organobismuth precursors are reported.…”
Section: Introductionmentioning
confidence: 78%
“…On the other hand, we have been involved in investigating the chemistry of higher analogues of phosphonic acids, namely organostibonic acids, and have investigated the reaction of organostibonic acids with various protic ligands. Interesting discrete molecular clusters displaying varied geometries such as a cube, a triangle, adamantane, tetrameric butterfly cores, and dodeca- and hexadecanuclear organoantimony-based POM frameworks , have been synthesized and structurally characterized. Very recently, investigations on the reactivity of organophosphonic acids with organostibonic acids have been carried out and structural characterization of the products revealed the formation of novel organostibonate phosphonate clusters of varying shapes and nuclearities.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 Very recently isolation of mixed valent Sb(V/III) POMs has been reported that are stabilized by telluroxane ligands. 7 With our continuing interest in the investigation of the reactivity of organostibonic acids, the reactivity of organostibonic acids with t-butylsilanetriol was investigated. Independently, organosilanols have been used as ligands for the generation of a variety of interesting cluster frameworks based on main group metals, 8 transition metals 9 and lanthanides.…”
Section: Introductionmentioning
confidence: 99%